2020
DOI: 10.1007/s11211-020-00357-6
|View full text |Cite
|
Sign up to set email alerts
|

Societal Actors Shape Collective Identities of Minorities: Procedural Fairness Climate Effects on Identification, Subjective Well-Being and Psychological Health

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer Science+Business Media, LLC, part of Springer Nature. This e-offprint is for personal use only and shall not be self-archived in electronic repositories. If you wish to selfarchive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 70 publications
7
20
0
Order By: Relevance
“…Specifically, we investigated whether procedural fairness emanating from the level of societal actors (macro‐level) “trickles down” on how racial events among citizens are understood and responded to in daily life (micro‐level), and, as such, indirectly impacts upon social trust in other citizens. By doing so, we extend Helms’ (1990) “interpersonal” model with the observation that institutional experiences can also shape racial socialization; and similarly, we add to Valcke, Van Hiel, Van Roey, et al.’s (2020) “institutional” model that interpersonal relations also play a role in the creation of social capital. Most importantly, our results therein align with a growing body of literature documenting the interplay and “spillover” effects between the collective and interpersonal levels of the social self (Baumeister & Leary, 1995; Kachanoff et al., 2019; Kachanoff et al, 2020; Valcke et al, 2020; Vignoles et al., 2006).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Specifically, we investigated whether procedural fairness emanating from the level of societal actors (macro‐level) “trickles down” on how racial events among citizens are understood and responded to in daily life (micro‐level), and, as such, indirectly impacts upon social trust in other citizens. By doing so, we extend Helms’ (1990) “interpersonal” model with the observation that institutional experiences can also shape racial socialization; and similarly, we add to Valcke, Van Hiel, Van Roey, et al.’s (2020) “institutional” model that interpersonal relations also play a role in the creation of social capital. Most importantly, our results therein align with a growing body of literature documenting the interplay and “spillover” effects between the collective and interpersonal levels of the social self (Baumeister & Leary, 1995; Kachanoff et al., 2019; Kachanoff et al, 2020; Valcke et al, 2020; Vignoles et al., 2006).…”
Section: Introductionmentioning
confidence: 80%
“…Of special relevance for the present research, Valcke et al. (2020) have shown that when societal institutions make procedurally fair decisions with respect to multicultural issues (which they define as “ethnic‐cultural, religious or linguistic issues”), this can positively affect minority members’ felt social trust.…”
Section: Introductionmentioning
confidence: 86%
“…In sum, our findings point toward procedural fairness by societal institutions as an important social engineering tool for ethnic minorities to identify with society at large. Moreover, they suggest that the influence of procedural fairness may well extend above and beyond mere identification processes, as feelings of societal belongingness have been linked to psychological well‐being (Valcke et al, 2020) and social behaviors that benefit society as well.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, fairness can be enacted toward individuals, as often studied in procedural fairness literature, but also toward entire social groups. It can reasonably be assumed that procedural fairness delivered to one’s social group by authorities at a superordinate level affects the collective self–that is, self‐representations pertaining to the group represented by the fairness enacting authority (Hornsey & Jetten, 2004)–and, accordingly, satisfies one’s collective belongingness needs (see, Valcke, Van Hiel, Van Roey, Van de Putte, & Dierckx, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As indicated in the introduction and the methodology, this study was considered an initial step in the analysis of the contextual variable collective self-esteem, incorporated along with other variables within a broader study, and whose main objective was to validate the scale in the Chilean school population and to report the main results measured in a diverse sample at the national level, hoping to be able to describe its effects based on the differentiation established from the administrative dependency, a critical issue in Chile and which represents a strength and contribution of the study considering that a representative sample of the target population was covered. Although the literature indicates that there are a number of other related variables based on broad constructs, or meta-constructs ( Torres et al, 2018 ; Huguley et al, 2019 ), related for example to the allocentric perspective ( Glaveanu, 2019 ) and welfare ( Valcke et al, 2020 ) that account for the normative interaction between the subjective and the collective dimension with a social ontological character ( Welch and Yates, 2018 ), they were not incorporated in this specific study, nor in the broader study of which it is a part, given that this was not the general objective established for the design of the project in general, as it considered the measurement of socio-emotional variables with a psychological and pedagogical development perspective, that influence student trajectories. The introduction of this type of variables would have widened the spectrum and objectives of study, exceeding therefore the initial vision closer to the educational field.…”
Section: Discussionmentioning
confidence: 99%